THE EFFECT OF ENTREPENEURSHIP INTEREST AND THE KNOWLEDGE OF WORK AND INDUSTRY ON THE WORK READINESS - Rusydi, Muhammad Ibnu; Nugraha, Hari Din; Munadi, Sudji (Universitas Pendidikan Indonesia, 2022)
The purpose of this study is to identify the effect of entrepeneurship interest on work readiness, the effect knowlegde of work and industry on the work readiness, and the effect of entrepeneurship interest and knowlegde of work and industry on work readiness of student class XII machining engineering in SMK Negeri 2 Pengasih. This research is an ex-post facto with quantitative descriptive research type. The population as a whole by 92 students of class XII machining engineering program. The samples used were 48 students. The sampling technique using the technique Probability Sampling. Data analysis technique used is simple regression analysis and multiple regression analysis. The results of this study are: The entrepeneurship interest had a positive and significant effect on work readiness with the value 23,9%; the knowlegde of work and Industry had a positive and significant effect on work readiness with a value 90,7%; Entrepeneurship interest and knowlegde of work and industry together have a positive and significant effect on work readiness with a value 91,5%.